Self-regulatory driving and riding practices amongst older adults in Malaysia. (April 2019) - Ang, Boon Hong; Lee, Shaun Wen Huey; Oxley, Jennifer; Yap, Khai Khun; Song, Keang Peng; Kamaruzzaman, S.B.; Chin, A.V.; Tan, K.M.; Khor, H.M.; Chen, Won Sun
Highlights: A pioneering study exploring self-regulatory practices amongst motorcycle riders. Motorcycle riders were found to be at risk of crash involvement and riding cessation. Behavioural and psychological factors were important contributors to self-regulation. Interventions should be customised to cater for populations with mixed travel modes. Abstract: Introduction: The ability to drive longer and safely are crucial for many older adults. There is a growing evidence on self-regulatory practices amongst older drivers in developed countries, but limited studies are conducted in developing countries. This study aimed to explore self-regulatory practices amongst older Malaysian car drivers and motorcycle riders. Materials and methods: A cross-sectional study was conducted amongst older adults aged 60 years and above residing in two states located in the west coast of Peninsular Malaysia using a self-administered questionnaire. Stepwise regressions were performed to identify for key factors associated with driving/riding self-regulation and crash involvement. Multilevel modelling was conducted to examine the clustering effect of respondents recruited from the two states. Results: Six-hundred and thirty-seven respondents completed the questionnaire, with over three-quarters of them still driving/riding at the time of data collection. Physical fitness, behavioural and psychological changes experienced with advancing age were important motivators towards self-regulation. Motorcycle riders were found to be at a higher risk of crash involvement, and they were more prone to cease riding compared to car drivers. Conclusions: Self-regulatory practices amongst older car drivers and motorcycle riders were found to be different. As such, there is a need to customise evidenced-based approaches to cater for specific age groups and road users, particularly in a developing country like Malaysia, where motorcycle is often considered as an affordable mode of transport and is largely involved in road traffic crashes.